Ascertaining universal features of yielding of soft materials - Kamble, Samruddhi; Pandey, Anurag; Rastogi, Sanjay; Lele, Ashish K. (Rheologica Acta, 2013)
Many metastable complex fluids, when subjected to oscillatory shear flow of increasing strain amplitude at constant frequency, are known to show a characteristic nonlinear rheological response which consists of a monotonic decrease in the elastic modulus and a nonmonotonic change in the loss modulus. In particular, the loss modulus increases from its low strain value, crosses the elastic modulus, and then decreases with further increase in the strain amplitude. Miyazaki et al. (Europhys Lett 75:915-921, 2006) proposed a qualitative argument to explain the origin of the nonmonotonic nature of the loss modulus and suggested that in fact this response could be universal to all complex fluids if they are probed in a certain frequency window in which the fluid is dominantly elastic in the small strain limit. In this letter, we confirm their hypothesis by showing that a wide variety of complex fluids, irrespective of their thermodynamic state under quiescent conditions, indeed show the aforementioned characteristic nonlinear response. We also show that the maximum relative dissipation during yielding occurs when the imposed frequency resonates with the characteristic beta relaxation frequency of the fluid.
Keywords: Colloidal suspensions; Entangled melts; Gels; Glasses; Microgels; Rheology; Yielding

High-performance sultone-modified PVA/PAMPS semi-IPN hydrogels for proton exchange membranes - Patwadkar, Manjusha V.; Illathvalappil, Rajith; Torris, Arun; Francis, Sifa C.; Kurungot, Sreekumar; Badiger, Manohar V. (Journal of Applied Polymer Science, 2026)
Hydrogel membranes composed of poly(2-acrylamido-2-methyl-1-propanesulfonic acid) (PAMPS) and sultone-modified poly(vinyl alcohol) (PVA) were successfully synthesized and evaluated as promising proton-conducting materials. A key advantage involves the premodification of PVA with 1,3-propane sultone to introduce sulfonic acid groups, thereby imparting proton conductivity to the PVA backbone. This sultone-modified PVA was then physically entangled within a PAMPS cross-linked network to form novel semi-interpenetrating network (semi-IPN) hydrogels. This synergistic design leverages the excellent film-forming and mechanical properties of PVA with the high proton conductivity inherent to PAMPS. The synthesized membranes exhibited robust mechanical properties, with tensile strengths ranging from 5 to 30 MPa and percentage elongations between 200% and 400%, depending on their humidity content. These hydrogel membranes demonstrated proton conductivities ranging from 0.6 to 4.3 x 10-2 S cm-1. The activation energy for proton conduction was found to be as low as 3.5 kJ mol-1, significantly lower than that of the commercial benchmark membrane, Nafion 117 (12 kJ mol-1). These findings underscore the potential of these novel PAMPS/sultone-modified PVA semi-IPN hydrogel membranes for advanced fuel cell applications.
Keywords: batteries and fuel cells; functionalization of polymers; Gels; membranes; polyelectrolytes

Simple two-step gelation process to strengthen 3D printed carboxy methyl cellulose gels - Rajput, Tejas; Sathe, Asmi; Gopal, Animesh; Sharma, Aakash; Shanmuganathan, Kadhiravan (Cellulose, 2026)
Carboxymethyl cellulose (CMC) is a water-soluble cellulose ether that is widely utilized in hydrogel applications due to its exceptional water absorption and biocompatibility. This study reports a simple two step strategy to make mechanically robust CMC gels without any additional chemical crosslinkers and how it could be leveraged to strengthen 3D printed CMC gels. These hydrogels, prepared through acid-induced gelation followed by freeze-thawing, exhibited a compressive modulus of 12.4 +/- 0.92 kPa and a compressive strength of 491.0 +/- 18.1 kPa. They could be leveraged for strengthening 3D printing hydrogels of intricate shapes by direct ink writing. Small amplitude oscillatory shear (SAOS) tests indicated an order of magnitude higher storage modulus for freeze-thawed gels (FC) as compared to only acid-induced CMC gels (HCMC). Nonetheless, stress relaxation experiments revealed that FC, as well as HCMC gels, relax at similar time scales. FC gels exhibited clear birefringence under crossed polarizers, indicating molecular ordering that is consistent with the presence of ordered/crystalline domains. Such ordered domains likely contribute to the higher elastic modulus and compressive strength observed in FC gels as compared to HCMC gels.
Keywords: 3D printing; Carboxymethyl cellulose; cellulose; Gels